The ministry of glory to glory Paul on preaching the gospel - Metevelis, Matthew (2018)
The most important job for any pastor is to proclaim the gospel, not only in sermons but in many aspects of their daily ministry. This is a complicated task, and one that is made more difficult by the differing contexts in which this proclamation takes place. Here, Paul’s admonition to the Christians at Corinth helps in discerning how this might be done.
Keywords: Bible. Corinthians II 1-7; Church work with stepfamilies; Pastoral Theology; Paul, Saint, Apostle; Prayer -- Christianity; Preaching -- Theory; Reader-response criticism